Evidence Brief: Enhancing Equitable Access to Assistive Technologies in Canada - Mattison, CA; Wilson, MG; Wang, RH; Waddell, K (My University, 2017)
An assessment of what is known about problems related to equitable access to assistive technologies, options for addressing these problems, and key implementation considerations. The evidence brief was an input to a stakeholder dialogue on the topic of enhancing equitable access to assistive technologies in Canada.
Keywords: enhancing; equitable; access; assistive; technologies; Canada